Effectiveness and outcomes of air travel-related TB incident follow-up: a systematic review. Issue 5 (6th May 2021) - Maynard-Smith, Laura; Brown, Colin Stewart; Harris, Ross Jeremy; Hodkinson, Peter; Tamne, Surinder; Anderson, Sarah Ruth; Zenner, Dominik
The World Health Organization (WHO) recommends following up passengers after possible exposure to a case of infectious tuberculosis (TB) during air travel. This is time-consuming and difficult, and increasingly so with higher numbers each year of flights and passengers to and from countries with high TB endemicity. This paper systematically reviews the literature on contact tracing investigations after a plane exposure to active pulmonary TB. Evidence for in-flight transmission was assessed by reviewing the positive results of contacts without prior risk factors for latent TB. A search of Medline, EMBASE, BIOSIS, Cochrane Library and Database of Systematic Reviews was carried out, with no restrictions on study design, index case characteristics, duration of flight or publication date. In total, 22 papers were included, with 469 index cases and 15 889 contacts. Only 26.4% of all contacts identified completed screening after exposure. The yield of either a single positive tuberculin skin test (TST) or a TST conversion attributable to in-flight transmission was between 0.19% (95% CI 0.13%–0.27%) and 0.74% (95% CI 0.61%–0.88%) of all contacts identified (0.00%, 95% CI 0.00%–0.00% and 0.13%, 95% CI 0.00%–0.61% in random effects meta-analysis). The main limitation of this study was heterogeneity of reporting. The evidence behind the criteria for initiating investigations is weak and it has been widely demonstrated that active screening of contacts is labour-intensive and unlikely to be effective. Based on our findings, formal comprehensive contact tracing may be of limited utility following a plane exposure. The evidence behind criteria for initiating airplane tuberculosis contact tracing is weak. It has been widely demonstrated that active screening is labour-intensive and unlikely to be effective. Formal, comprehensive contact tracing may be of limited utility. https://bit.ly/2U1ebHI